Rozwiązania Równań Różniczkowych n-tego Rzędu Występujących w Mechanice - Wierzcholski, K. (Engineering Transactions, 1972)
The paper discusses the solution of linear n-order differential equations in which variable· coefficients are polynomials. We especially consider solutions of 2-nd and 4-th order equations. which occur in mechanics. The received results are applied to determine the bending line of the bar with a variable moment of inertia.